Let's break down the steps given in the directions and work backward to identify the original equation.
-
The final answer is \( x = 8 \).
-
According to the directions, before we arrive at \( x = 8 \), we need to first undo the multiplication by -2. If we have \( x = 8 \), we multiply both sides by -2, we would have: \[ -2x = -16 \]
-
Now, we need to add 5 to both sides, which means we would have: \[ -2x + 5 = -16 + 5 \] This simplifies to: \[ -2x + 5 = -11 \]
-
To summarize, the original equation before any operations were performed appears to be: \[ -2x + 5 = -11 \]
Thus, the equation that is solved correctly, following the given steps, is: \[ -2x + 5 = -11 \]